Economic Order Quantity and Supply Chain Performance of County Governments in Western Region, Kenya - Oboge, Odiwuor David; Kwendo, Evans; Odero, Jackline Akoth (Research Collaboration Community (RCC), 2024)
Many organizations have realized the significant role played by Economic Order Quantity in determining Supply Chain performance. This study sought to examine the effect of economic order quantity on supply chain performance in county governments in western region, Kenya. This study adopted descriptive survey research design targeting 120 respondents from the procurement, stores and quality assurance departments. Data was obtained using structured questionnaires and analyzed using descriptive and inferential statistics. Descriptive statistics used were: mean, frequency percentage and standard deviation while for Inferential statistics Pearson correlations and simple linear regression was used. The regression results established that Economic Order Quantity had a positive and significant effect on the Supply chain performance of County Governments in Western Region, Kenya. (β= 0.762; p< 0.000). The findings extends knowledge on inventory management practices and specifically on economic order quantity that can enhance performance. The study recommends for County Governments to adopt as well as integrate Economic Order Quantity (EOQ) into its supply chain strategies.